Globalisation in Mirror Images : Westernisation in India, Easternisation in the Netherlands - Rutten, Mario (The Netherlands:Provincial Globalisation is a collaborative international research programme of the Amsterdam Institute for Social Science Research (AISSR), University of Amsterdam, and the National Institute of Advanced Studies (NIAS), Bangalore, India)
Koleksi Referensi (Tidak Dipinjamkan)